Effects of added choline on performance of weanling pigs - K Hongtrakul; I H Kim; J A Loughmiller; J W Smith; H Cao; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1996)
A 28-d growth assay was conducted to determine the effects of added choline on weanling pig performance. Pigs were fed a control diet without added choline or diets containing 150 g/ton of added choline. No differences in pig growth performance were observed. These results suggest that added choline can be removed from weanling pig diets.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Weanling pigs; Choline